Fannie Bloomfield-Zeisler : the life and times of a piano virtuoso - Macleod, Beth Abelson, 1945- (Music in American life., 2015)
One of the foremost piano virtuosi of her time, Fannie Bloomfield-Zeisler reliably filled Carnegie Hall. As a "new woman," she simultaneously embraced family life and forged an independent career built around a repertoire of the German music she tirelessly championed. Yet after her death she faded into obscurity. In this new biography, Beth Abelson Macleod reintroduces a figure long, and unjustly, overlooked by music history. Trained in Vienna, Bloomfield-Zeisler significantly advanced the development of classical music in the United States. Her powerful and sensitive performances, both in recital and with major orchestras, won her followers across the United States and Europe and often provided her American audiences with their first exposure to the pieces she played. The European-style salon in her Chicago home welcomed musicians, scientists, authors, artists, and politicians, while her marriage to attorney Sigmund Zeisler placed her at the center of a historical moment when Sigmund defended the anarchists in the 1886 Haymarket trial. In its re-creation of a musical and social milieu, Fannie Bloomfield-Zeisler paints a vivid portrait of a dynamic artistic life